A simple optical frequency comb generator based on the monolithic integrated dual-tone semiconductor laser subject to the gain-switching effect - Li, Jin; Zheng, Jinlin; Pu, Tao; Zhou, Hua; Zhang, Xin; Li, Yunkun; Zhu, HuaTao (2021 19th International Conference on Optical Communications and Networks (ICOCN), 2021)
A simple photonic approach to generating the wideband optical frequency comb (OFC) based on the monolithic integrated dual-tone semiconductor laser (MI-DTSL) subject to the gain-switching effect is proposed and experimentally demonstrated in this work. The impressive hotspots focus on that different from the traditional single-section laser, the MI-DTSL naturally owns dual-wavelength state attributing to the two DFB laser sections integrated on one chip. Thus, when the MI-DTSL is injected with large RF signal, all optical wavelengths in the integrated cavity would be simultaneously modulated and go into the gain-switching effect, leading to the generation of the wideband OFC compared to one single-section laser attributing to the wavelengths of the dual lights are not distant. In addition, as a result of high integration of the MI-DTSL, the system would be rather low-cost, flexible and convenient. In the experiment, one discernible OFC with a bandwidth of 115 GHz and a comb line of 23 within 10-dB amplitude variation is obtained and it is the twice than that by using the gain-switching single-section laser, largely suggesting this method huge effectiveness.